New Insights on Biosynthesis of Nanoparticles Using Plants Emphasizing the Use of Alfalfa (Medicago sativa L.) - Inese Kokina; Ilona Plaksenkova; Lauris Jankovskis; Marija Jermaļonoka; Renata Galek (Journal of Nanotechnology)
Biological synthesis of nanoparticles (NPs) using alfalfa (Medicago sativa L.) and other plants has several advantages such as lower costs, reduction of pollution, and improvement of the environment and human health. Often, biosynthesis is used to synthesize Ag, Au, and ZnO NPs. Less often are also synthesized Cu and Fe NPs. Synthesis with plant extracts from their parts or callus cultures is a widely used method since extracts contain the most significant number of biomolecules. Synthesis with living plants (in vivo) provides NPs with improved properties for better interactions with plants but is used less often due to the long realization time, the need to control the plants’ growing conditions, and difficulty in controlling the size and shape of the synthesized NPs. Here, we performed a systematic review of various methods for the biological synthesis of different metal NPs with different plants, to highlight advantages and disadvantages of mentioned methods. For discussion, results showed that biosynthesis of NPs allows obtaining NPs with reduced toxicity, and their size and shape depend on the type and number of biomolecules present in plants. Plant biomolecules determine the antibacterial and anticancer properties of NPs, as well as increasing the use of NPs in biomedicine, for better drug transport, therefore medicinal plants or sea plants are mostly used for biosynthesis. NPs which were synthesized in marine plants could be a very effective agent against water bacteria; therefore, if NP biosynthesis takes place in water, biological water purification is possible. Limitations of the study included a great methodological diversity of the synthesis, it is still difficult to systematize the synthesis methods, and it seems that each described study uses a different synthesis protocol; therefore, in future studies, it is necessary to clarify which method can provide the most efficient biosynthesis and develop a unified approach.